2020
DOI: 10.1186/s41239-020-00222-1
|View full text |Cite
|
Sign up to set email alerts
|

A quasi-qualitative analysis of flipped classroom implementation in an engineering course: from theory to practice

Abstract: Students have different learning approaches and acquire knowledge in different ways owing to their varied perceptions and grasping abilities. Treating students equally, following the traditional teacher-cantered approach, may not be effective and calls for innovations in knowledge dissemination. This article takes a student-centric approach to implement a ‘flipped classroom’ model in an engineering course for constructivism (i.e. experience-based learning), and students’ personalized learning. The performance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
15
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 27 publications
2
15
0
3
Order By: Relevance
“…Advantages of flipped learning were also mentioned by Nielsen (2020), who stated that educators are enabled to carry out their experiments with the help of flipped learning to reinforce learning of students and changing their study habits. This also was supported by Hussain et al (2020) who reported that flipped learning approach in the classroom enhances student's engagement with their teachers and peers. Jdaitawi (2020) also reported that flipped learning assist students in engaging in improving their connectedness and foster leisure attitudes.…”
Section: Wwwpsychologyandeducationnetmentioning
confidence: 66%
See 3 more Smart Citations
“…Advantages of flipped learning were also mentioned by Nielsen (2020), who stated that educators are enabled to carry out their experiments with the help of flipped learning to reinforce learning of students and changing their study habits. This also was supported by Hussain et al (2020) who reported that flipped learning approach in the classroom enhances student's engagement with their teachers and peers. Jdaitawi (2020) also reported that flipped learning assist students in engaging in improving their connectedness and foster leisure attitudes.…”
Section: Wwwpsychologyandeducationnetmentioning
confidence: 66%
“…This finding may be linked to the general premise that technology, with the use of flipped learning model, responds effectively to engineering students. Furthermore, flipped learning plays a key role in improving the social skills and interaction among students and teachers and their motivation (e.g., Hussain et al, 2020). In addition, peer and teacher interactions at its best motivate the students, maximize their engagement, and improve the development of other skills.…”
Section: Wwwpsychologyandeducationnetmentioning
confidence: 99%
See 2 more Smart Citations
“…A new method based on fuzzy logic is designed to evaluate students' survey responses from qualitative survey data. The flipped classroom model helps students improve their grades and strengthen their interaction with teachers and peers [7]. The results of these studies may all help other scholars to strive to achieve personalized learning based on experience and students, but their research is not comprehensive.…”
Section: Introductionmentioning
confidence: 99%